ANALISIS PERMODALAN DAN KEUNTUNGAN USAHA MIKRO KECIL MENENGAH PADA RUMAH MAKAN (STUDI KASUS) DI KOTA MANADO - Freddy Huibert Jacob Panelewen; Wenny Tilaar; Jolanda Kitsia Juliana Kalangi (Sam Ratulangi University, 2020)
This study aims to analyze business management based on business methods and the effect of capital on the profits of MSME restaurants. This research was conducted in March to June 2019 in Manado City, North Sulawesi Province. The selection of respondents is done deliberately (purposive sampling). Primary data collection was carried out by interviewing 50 SME restaurant business owners. Secondary data were obtained from related agencies and journal articles. The analysis is carried out by analyzing the capital management of the profits of the restaurant business (business method of business) per year and analyzing the effect of capital on profits affected by costs and revenues (using SPSS Ver.22). The results showed that the capital and wealth per year, the smallest amounted to Rp 200,000.- and the highest capital and wealth Rp 107,100,000. While the average capital and wealth of micro and small restaurant businesses is Rp.10,862,360.- per year. Costs incurred per year, the lowest amounted to Rp. 800,000.- and costs incurred the highest Rp. 161,920,000. While the average annual costs incurred by micro small and medium restaurant businesses are Rp. 31,897,600. - The lowest receipts received were Rp. 24,675,000. - and the highest received receipts were Rp. 33,000,000,000. - While the average annual revenue received by micro and small restaurant restaurants was Rp. 1,463,471,300, - Profits obtained per year, the lowest is Rp. 60,300,000. - and the highest profit is Rp. 6,000,000,000. 800, - The calculation results from the data collected produce Regression Equation Y = 863,536.6,537 + 5,011X1 + 3,690X2 + 0,146X3. This states that the hypothesis is accepted that capital and wealth, costs and revenues have a very significant effect on profits (confidence level of 99%).*eprm*